A technique to improve optical time division multiplexing - wavelength division multiplexing performance - Hiew, C. C.; Abbou, F. M.; Chuah, Hean Teik; Abdul Rashid, Hairul Azhar (The Institute of Electronics, Information and Communication Engineers, 2005)
Optical time division multiplexing - wavelength division multiplexing (OTDM-WDM), intensity modulation (IM) systems employing optical amplification and dispersion management (DM) are analyzed with and without the introduction of an optical narrowband bandpass filter placed right after optical time demultiplexing. The use of the filter was found to improve the performance of the demultiplexed channels by reducing amplitude jitter while possessing high intersymbol interference (ISI) tolerance. The OTDM-WDM link shows good performance up to 2000 km with the OTDM filter providing a Q gain of 0.7-1.1 dB. The optimal input power reduces for longer distances due to increased significance of nonlinear effects. A 900 km link showed good performance for spectral efficiencies as low as 0.52 bits/s/Hz, though the Q gain provided by the OTDM filter reduces as channel spacing decreases.